Effects of Antenatal Dexamethasone on Respiratory Distress in Late Preterm Infant: A Randomized Controlled Trial - Nipawan Attawattanakul; Pimpika Tansupswatdikul (The Royal Thai College of Obstetricians and Gynaecologists, 2015)
Objective:To determine the effects of antenatal dexamethasone on rate of respiratory distress in late preterm infant comparing with non-dexamethasone.Study design: Opened label randomized controlled trial.Method: 194 singleton pregnant women who were admitted to Chonburi Hospital due to preterm labor from March 2013 to March 2014 were randomized by block of four method into two groups. The study group (n = 96) was prescribed dexamethasone 6 mg intramuscularly every 12 hours for totally 4 doses or until delivery and control group (n = 98) who not receive dexamethasone. Rate of neonatal respiratory distress, morbidity and mortality were assessed and analyzed by Unpaired T-test, Mann Whitney U-test and Chi-square test between both groups.Results:The study showed that rate of neonatal respiratory distress was statistically significant lower in study group, 9 cases (9.4%) compared with control group, 20 cases (20.4%). (p = 0.03, relative risk = 0.40, confidence interval = 0.17 to 0.94). Anyway, the need for respiratory support and the need of intensive unit care were not different, (p = 0.07, 0.05, respectively).Conclusion: Administration of dexamethasone in late preterm labor pregnancies significantly decreased the rate of respiratory distress.